2016
DOI: 10.3354/cr01373
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological cycle, temperature, and land surface-atmosphere interaction in the La Plata Basin during summer: response to climate change

Abstract: The austral summer response (2071−2100 with respect to 1981−2010) in terms of precipitation, temperature, and evapotranspiration was analyzed over South America, with emphasis on the La Plata Basin (LPB), using an ensemble of regional climate models. Seasonal mean precipitation increased over the southern LPB, consistent with CMIP3 and CMIP5 ensembles. However, the region of wetting (in the sense of precipitation minus evapotranspiration) over the LPB shifts to the north and northwest, compared to the region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Moreover, they stated that these results were due to the cancelation of offsetting errors in the individual models. Menéndez et al [37] found that the ensemble seasonal (December, January and February, DJF) mean precipitation compared to the CPC-Unified Gauge-Based data [45] is underestimated in the southern LPB down to 3 mm/day and it is overestimated in the northern and eastern LPB up to 4 mm/day. Solman et al [38] found that although the results of the ensemble of the RCMs systematically improved the quality of the modelled climate compared to the single RCM model evaluated in the CLARIS-LPB project, they did not identify anyone producing systematically worse or better results for every variable over every region.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, they stated that these results were due to the cancelation of offsetting errors in the individual models. Menéndez et al [37] found that the ensemble seasonal (December, January and February, DJF) mean precipitation compared to the CPC-Unified Gauge-Based data [45] is underestimated in the southern LPB down to 3 mm/day and it is overestimated in the northern and eastern LPB up to 4 mm/day. Solman et al [38] found that although the results of the ensemble of the RCMs systematically improved the quality of the modelled climate compared to the single RCM model evaluated in the CLARIS-LPB project, they did not identify anyone producing systematically worse or better results for every variable over every region.…”
Section: Introductionmentioning
confidence: 99%
“…The most ambitious collaborative initiative for producing ensembles of RCM simulations over the La Plata Basin was performed within the CLARIS-LPB Project (a Europe-South America network for climate change assessment and impact studies [42,43]). A suite of seven coordinated RCM simulations over South America (with an approximate grid resolution of 50 km) driven by both the ERA-interim [44] reanalysis and a set of GCMs were evaluated [34,[36][37][38][39][40]42]. Carril et al [36] found relatively good agreement for the annual precipitation average cycle over the La Plata Basin by applying an ensemble of RCMs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations